Effective use of marketing technology in Eastern Europe: Web analytics, social media, customer analytics, digital campaigns and mobile applications - Jayaram, Dureen (2015)
The transition economies of Eastern Europe present both the opportunities and challenges for companies operating in these markets. On one hand, these countries have a large number of technology savvy young consumers, and on the other, the markets must also take into consideration the macro-environment of a country and market conditions which make the use of certain market technologies more feasible and attractive compared to others. It is certainly true in terms of the timing for introduction of various technologies in a country. Drawing analogy for the “IDITAROD RACE” we develop three different “Sled Dog Team layouts” for market characteristics and technologies for three Eastern European countries, namely, Slovakia, Bulgaria, and Albania. The ten market characteristics included in our research are: digital connectivity divide, economic power, demand type, privacy laws, demographics, and competitive conditions, attitude towards technology, institutional maturity, corporate social responsibility, and corruption. The ten marketing technologies included in our research are: digital profiling, segmentation, websites, and search engines marketing, campaign management, content management, social media, mobile application, digital collaborations, and analytics. Company case studies are analyzed and reported for each of these three countries which support the three models presented in our research. Doi: http://dx.doi.org/10.1016/j.jefas.2015.07.001